Comparative Study for Different Types of Shear Walls in Buildings Subjected to Earthquake Loading - Husain, Muhammed Abbas; Mahmood, Osamah Ibrahim (Al-Nahrain Journal for Engineering Sciences, 2017)
Shear walls are effective structural elements used mainly in multi-story buildings to provide resistance against lateral loadings such as earthquake and wind loadings. There are several types and shapes of shear walls depending mainly on geometry and height of the building. Both type and shape of the shear wall affect the efficiency of resisting lateral loadings. In this study, fifty six building models have been analyzed using the finite element method by using the SAP2000 V14 computer program. Each model have ten stories, subjected to earthquake loadings, with various numbers of bays, and with three types of shear walls, namely: side shear walls, middle shear core, and double shear cores, provided that each type of the shear walls (or cores) has the same material volume. The analysis outputs have been investigated to select the appropriate type and location of the shear walls (or cores) for the multi-story buildings subjected to earthquake loadings. Specified conclusions have been presented to obtain the optimum behavior for the multi-story buildings under the effects of earthquake loadings.